A method of analysis of the shapes of X-ray diffraction lines not requiring a transition to the space of an object - Rozhenko, N.M.; Grigor’ev, O.N.; Kartuzov, V.V. (Reports of the National Academy of Sciences of Ukraine, 2019)
Generalizations of the method of moments and the Hall—Williamson one are presented without a priori assumptions about the distribution law for microstrains with regard for the nature of a dispersion function due to the presence of coherent scattering. The developed approach is based on the analysis of the shape of the complete physical profile restored using the Tikhonov regularization method and allows one to determine the distribution function of microstrains.